CECO wave energy converter: concept and physical model tests - Paulo Rosa Santos (2014)
A new wave energy converter was designed to absorb simultaneously both the kinetic and the potential wave energy, and it is being developed at the Hydraulics Laboratory of the Faculty of Engineering of the University of Porto. The paper presents results obtained in the first and second phase of the experimental study and compares them taking into account the improvements introduced in the model and the techniques used to evaluate the absorbed power. Test conditions included different sea states and power-takeoff damping levels. The analysis is based on CECO response, mean absorbed power and corresponding relative capture widths. Two different techniques were used to evaluate the power absorbed (direct and indirect methods). The potential of this new concept was confirmed as relative capture widths of up to 30% were obtained in the second phase of the study with a physical model not yet fully optimized.